Breaking Barriers: Digital Marketing and Social Media as Catalysts for Women Entrepreneurship in Uzbekistan - Uygunova Odinabonu Ilkhom qizi (Zien Journals, 2023)
Women entrepreneurs are breaking barriers and making their mark in the business world, even in regions where traditional gender roles have prevailed. In Uzbekistan, a country with a rich cultural heritage, women are leading the charge in the startup landscape. This article explores the dynamic intersection of digital marketing, social media strategies, and women-led startups in Uzbekistan. By examining the perspectives of women entrepreneurs, digital marketing strategies, social media's impact, and the challenges they face, we uncover the keys to their success and the potential for economic growth and empowerment.
Keywords: digital marketing; social media marketing; women entrepreneurs; women-led startups